THE IMPACT OF CLIMATE CHANGE ON CUSTOMS REVENUES IN THE WAEMU ZONE - Soro, Segba Jean (Jurnal BPPK: Badan Pendidikan dan Pelatihan Keuangan, 2023)
In recent years, the planet has been marked by major events: immigration, terrorism, armed conflicts and above all global warming which is attracting the attention of countries around the world and those of WAEMU in particular. Global warming leads to disruptions in the functioning of production cycles. Indeed, these countries which are essentially agricultural are facing several phenomena. The impact of climate change on customs revenues in the West African Economic and Monetary Union (WAEMU) area refers to the effects that climate variations, such as increased temperatures, extreme weather events, rising of sea level and changes in precipitation, can have on the revenue generated by customs activities in this region. Agricultural production is falling sharply. This inevitably leads to a reduction in customs revenue. Customs revenues constitute the main means of development for these countries. This question is of capital importance insofar as it obliges States to adopt new policies. They should diversify areas of production and think about transforming products in order to increase added value. Furthermore, WAEMU States would benefit from taking an increasing interest in industrialization policies in order to minimize imports which weigh heavily on the trade balance because the effects of global warming will continue to grow.